2013
DOI: 10.1007/s10456-013-9393-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inflammatory cytokines on lymphatic endothelial barrier function

Abstract: Proper lymphatic function is necessary for the transport of fluids, macromolecules, antigens and immune cells out of the interstitium. The lymphatic endothelium plays important roles in the modulation of lymphatic contractile activity and lymph transport, but it's role as a barrier between the lymph and interstitial compartments is less well understood. Alterations in lymphatic function have long been associated with edema and inflammation although the integrity of the lymphatic endothelial barrier during infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 53 publications
7
112
0
1
Order By: Relevance
“…efflux of leukocytes, macromolecules, and plasma filtrate; Cromer et al 2014;Alitalo and Carmeliet 2002). As is the case with blood vascular endothelial cells, it has been described that several of the inflammatory cytokines elevated in the current study (e.g., IL-1b, IL-6, and TNF-a) can increase lymphatic endothelial cell permeability in vitro (Cromer et al 2014).…”
Section: Discussionmentioning
confidence: 57%
“…efflux of leukocytes, macromolecules, and plasma filtrate; Cromer et al 2014;Alitalo and Carmeliet 2002). As is the case with blood vascular endothelial cells, it has been described that several of the inflammatory cytokines elevated in the current study (e.g., IL-1b, IL-6, and TNF-a) can increase lymphatic endothelial cell permeability in vitro (Cromer et al 2014).…”
Section: Discussionmentioning
confidence: 57%
“…High HOXD10 expression resulted in abnormal junctions and increased permeability, whereas HOXD10 depletion resulted in reduced permeability through LEC monolayers. Currently, the role of VEGFR-3 signaling in regulating LEC permeability in vitro is not entirely clear, with some reports showing a reduction in transendothelial electric resistance of LECs after stimulation with VEGF-C (Breslin et al, 2007;Tacconi et al, 2015), whereas others found no effect of VEGF-C156S on macromolecular permeability (Cromer et al, 2014). Therefore, it is possible that wild-type VEGF-C induces permeability by activating VEGFR-2, whereas specific VEGFR-3 activation by VEGF-C156S has no such effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that obesity and metabolic syndrome might impair lymphatic function via changing the levels of inflammatory stimuli that might alter endothelial barrier functions or diminish the contractility of lymphatic vessels [34]. For instance, Scallan and colleagues [35,36] reported that impaired nitric oxide signalling was responsible for lymphatic vascular disruption in type 2 diabetes and that the contractility of collecting lymphatic vessels was improved upon genetic deletion of basal nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%